Faktor-faktor yang mempengaruhi kesejahteraan masyarakat muslim Kabupaten Semarang - Pratiwi, Septia Ayum; Pratama, Abdul Aziz Nugraha (Nur Science Institute, 2021)
This study aims to determine the effect of religiosity, income, and family members on people's welfare with consumption patterns as an intervening variable in Muslim communities in Semarang Regency. The research method is descriptive quantitative with 100 samples from Muslim residents in Semarang Regency based on questionnaire answers and processed using multiple linear analysis methods. The results show that religiosity and consumption patterns positively and significantly affect welfare. Meanwhile, income and the number of family members do not affect welfare. Simultaneously, the variables of religiosity, revenue, number of family members, and consumption patterns have a positive and significant effect on welfare. Path analysis concluded that consumption patterns could mediate the influence of religiosity, income, number of family members on the interest of the Muslim community in Semarang Regency.